2023
DOI: 10.1126/sciadv.adf6198
|View full text |Cite
|
Sign up to set email alerts
|

A radio pulsar phase from SGR J1935+2154 provides clues to the magnetar FRB mechanism

Abstract: The megajansky radio burst, FRB 20200428, and other bright radio bursts detected from the Galactic source SGR J1935+2154 suggest that magnetars can make fast radio bursts (FRBs), but the emission site and mechanism of FRB-like bursts are still unidentified. Here, we report the emergence of a radio pulsar phase of the magnetar 5 months after FRB 20200428. Pulses were detected in 16.5 hours over 13 days using the Five-hundred-meter Aperture Spherical radio Telescope, with luminosities of about eight decades fain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Consequently, the repeating FRB 20200120E would be classified as a nearby apparent one-off FRB if it were placed at a distance of 10s of Mpc. The same could be said for SGR 1935+2154 3,4,16,19,20 .…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Consequently, the repeating FRB 20200120E would be classified as a nearby apparent one-off FRB if it were placed at a distance of 10s of Mpc. The same could be said for SGR 1935+2154 3,4,16,19,20 .…”
mentioning
confidence: 81%
“…The datasets of radio pulses in this research are follows: (1) other bursts from FRB 20200120E, observed by CHIME 5 , DSS-63 17 , and Effelsberg telescopes 6, 10 ; (2) three well-studied localized repeating FRBs: FRB 20121102A 7 , FRB 20201124A 8 and FRB 20180916B 18,36,37 ; (3) radio bursts or pulses from the Galactic magnetar SGR 1935+2154 3,4,16,19,20 using a distance of 6.6 kpc; (4) a sample of super-giant pulses from the Crab pulsar 26 ; (5) single pulses of RRATs (RRATalog), and (6) pulsars at 1400 MHz 38 . For pulsars and RRATs, we presented the average properties of pulses from these sources.…”
Section: Bursts Of Frb 20200120e From Different Telescopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the first Galactic fast radio burst FRB 20200428 was detected from the magnetar SGR 1935 + 2154 (Bochenek et al 2020;CHIME/FRB Collaboration et al 2020), establishing that magnetars are one channel to produce FRBs. Radio pulses with a large range of strengths were found from this magnetar, FRBs being just the high fluency outliers (Pleunis & CHIME/FRB Collaboration 2020; Kirsten et al 2021;Zhu et al 2023). It is conceivable that other magnetars may also emit FRBs.…”
Section: Introductionmentioning
confidence: 86%
“…The pulses are found to be confined in a narrow phase window. FRB bursts, on the other hand, appear in random rotation phases, suggesting that the bursts and pulses likely originate from different locations and probably have somewhat different mechanisms (albeit sharing similar physics) [18]. • Cosmological FRBs are observed to have two apparent types: repeaters and nonrepeaters.…”
Section: The Source(s) Of Frbsmentioning
confidence: 99%